2016
DOI: 10.1002/jsfa.7908
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization and immunoregulatory activity of a polysaccharide isolated from Hibiscus sabdariffa L.

Abstract: The results indicated that HSP41 up-regulated the immune response by stimulating RAW264.7 cell activity. HSP41, a promising immunoregulator, possibly contributes to the health benefits of H. sabdariffa and might have potential applications in health food or medicine. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…They are important components involved in many physiological functions in all living organisms. Recently, more and more experiments have indicated that polysaccharides possessed a large range of pharmacological and biological properties, including antitumor, antidiabetic, antioxidant, anti‐inflammatory, and immunomodulatory activity and so on (Song, Li, Hu, Ni, & Li, ; Wang et al, ; Zheng et al, ). In addition, the polysaccharides were widely used in functional food and pharmaceutical industries for no toxic side effects (Xie et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…They are important components involved in many physiological functions in all living organisms. Recently, more and more experiments have indicated that polysaccharides possessed a large range of pharmacological and biological properties, including antitumor, antidiabetic, antioxidant, anti‐inflammatory, and immunomodulatory activity and so on (Song, Li, Hu, Ni, & Li, ; Wang et al, ; Zheng et al, ). In addition, the polysaccharides were widely used in functional food and pharmaceutical industries for no toxic side effects (Xie et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we hypothesized that the decreased cell viability and phagocytic capacity of I01-2 and I01-4 with an increase in concentration from 400 μg/mL or 1000 μg/mL, respectively, might be caused by an excessive build-up of NO in macrophages. Additionally, the NO levels in groups receiving EPS treatments were weaker than those in the group receiving LPS treatments, indicating that the EPS effects were more moderate than that of LPS [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prebiotic effect of arabinoxylan oligosaccharide isolated from wheat ( 28 ), antihyperglycemic effects of polysaccharide extracted from Memordica charantia ( 29 ), Inonotus obliquus ( 30 ), Hericium erinaceus ( 31 ), Ophiopogon japonicas ( 32 ), immune-modulatory effect of polysaccharide from Hibiscus sabdariffa L . ( 33 ), antioxidantive potential of polysaccharide from Euryale ferox Salisb. ( 34 ), antitumor effect of polysaccharide from Polygonum multiflorum ( 35 ) and other therapeutic efficacies of polysaccharides and oligosaccharides were investigated in the literature.…”
Section: Discussionmentioning
confidence: 99%